Adaptasi Peran Musyrifah Pengabdian (Studi Kasus Darul Marhamah Al-Qur’an Boarding School Makassar) - Arlifia Risky Adinda; Ahmad Yasser Mansyur; Haerani Nur (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to gain an in-depth understanding of the adaptation of the role of female religious teachers at the Darul Marhamah Al-Qur'an Islamic Boarding School in Makassar, identify and analyze the factors that influence the adaptation of the role of female religious teachers, identify changes in the role of female religious teachers as a result of the impact they experience, and identify ’an Boarding School in Makassar, identifying and analyzing the factors influencing the adaptation of the role of musyrifah pengabdian, identifying changes in the role resulting from the impact experienced by musyrifah pengabdian, and describing and analyzing the strategies used by musyrifah pengabdian in facing various challenges in role adaptation. Service-oriented musyrifah are students who, after completing their studies, are assigned to serve for one year as a requirement for receiving their diploma. This study employs a qualitative approach using the case study method. The research subjects were five female religious educators undergoing service at the boarding school, who were analyzed using thematic analysis. The results showed that the female religious educators underwent a gradual adaptation process through self-control, real-life experiences, and self-potential exploration. Adaptation was influenced by both internal and external factors, and the service produced both positive and negative impacts, leading to adaptation strategies including emotion-focused coping. The boarding school requires a more structured and supportive service system, as well as initial training and strengthening of coping skills, and further research on other boarding school institutions.